Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

From the book,
Suppose $p \equiv 1 \pmod{4}$, then by law of quadratic reciprocity, we have: $$\left(\frac{3}{p}\right) = \left(\frac{p}{3}\right) $$ Next, if $p \equiv 2 \pmod{3}$, then $p \equiv 5 \pmod{12}$ Hence, $$\left(\frac{3}{p}\right) = \left(\frac{p}{3}\right) = -1$$

How do they get those Legendre fraction equal to $-1$? From my understanding: $$\left(\frac{q}{p}\right) \cdot \left(\frac{p}{q}\right) = (-1)^{\frac{p-1}{2}\cdot\frac{q-1}{2}}$$ So $q = 3 \implies \frac{q-1}{2} = \frac{3-1}{2} = 1$ For $p$, I take $p \equiv 5 \pmod{12} \implies p = 5 + 12k$, for some integers k.
Hence, $\frac{p-1}{2} = \frac{12k + 5 - 1}{2} = \frac{12k + 4}{2} = 6k + 2.$ And this $6k + 2$ is even :( ! How does $(-1)^{even} = -1$?
Any idea? I think I made some logic mistakes somewhere, but I couldn't find where.

The problem was from Elementary Number Theory and Its Application - Kenneth H.Rosen 5th Edition.

Using the law of quadratic reciprocity, show that if $p$ is an odd prime, then $$\left(\frac{3}{p}\right) = 1 \text{ if } p \equiv \pm 1 \pmod{12}$$ $$\left(\frac{3}{p}\right) = -1 \text{ if } p \equiv \pm 5 \pmod{12}$$

Solution enter image description here Thanks,

Now I'm even more confused :(!
Consider two cases:
Case 1 $$p \equiv 1 \pmod{4} \text{ and } p \equiv 1 \pmod{3}$$ Then,
$$p \equiv 1 \pmod{12} \implies p = 12k + 1$$
$$\frac{p - 1}{2} \cdot \frac{3 - 1}{2} = \frac{12k}{2} = 6k = \text{ even }$$
Which implies
$$\left(\frac{3}{p}\right) \cdot \left(\frac{p}{3}\right) = 1$$
So both must be $1$ or $-1$.

Case 2 $$p \equiv 1 \pmod{4} \text{ and } p \equiv 2 \pmod{3}$$ Then,
$$p \equiv 5 \pmod{12} \implies p = 12k + 5$$
$$\frac{p - 1}{2} \cdot \frac{3 - 1}{2} = \frac{12k + 4}{2} = 6k + 2 = 2(3k + 1) = \text{ even }$$ Which implies
$$\left(\frac{3}{p}\right) \cdot \left(\frac{p}{3}\right) = 1$$ So both must be $1$ or $-1$.

I don't see how these arguments can be deduced to the solution. Any suggestion?

share|cite|improve this question
Please cite the "book" and page number. – Bill Dubuque Mar 28 '11 at 23:59
It's called the "Legendre symbol", not the "Legendre fraction". – Arturo Magidin Mar 29 '11 at 3:13
@Bill Dubuque: See my edit. Thank you. @Arturo Magidin: Thank you. – Chan Mar 29 '11 at 3:39
up vote 3 down vote accepted

I believe you can find the value of $(3|p)$ without finding $p\equiv 5\pmod{12}$, by use of the second supplement to quadratic reciprocity. Recall that $$ \left(\frac{2}{p}\right)=(-1)^{(p^2-1)/8}. $$ Since $p\equiv 2\pmod{3}$, you then have $(p|3)=(2|3)=-1$. So altogether, $$ \left(\frac{3}{p}\right)\left(\frac{p}{3}\right)=\left(\frac{3}{p}\right)\left(\frac{2}{3}\right)=\left(\frac{3}{p}\right)(-1)=(-1)^{(p-1)(3-1)/4}=(-1)^{(p-1)/2}=1 $$ This implies $(3|p)=-1$.

share|cite|improve this answer
Many thanks. Now I got it ;). – Chan Mar 29 '11 at 4:03

If $p\equiv 2 \mod 3$ then $p$ is not a square mod $3$. That is the justification for the second line.

As you correctly calculated, if $p$ is $5 \mod 12$ (and $q$ is odd) then $(-1)^{\frac {p-1}{2} \cdot \frac {q-1}{2}}$ is $(-1)^{\text{even}} = 1$.

You have an incorrect statement of the main case of quadratic reciprocity, for $p$ and $q$ odd primes. Instead of an equal sign between $(\frac p q)$ and $(\frac q p)$ there should be no symbol, or perhaps $\times$. The product $(\frac p q) (\frac q p)$ equals $(-1)^{\frac {p-1}{2} \cdot \frac {q-1}{2}}$, which is to say the product is $1$ except when $p$ and $q$ are both $3 \mod 4$, in which case it is $-1$.

share|cite|improve this answer

Personally I find that a huge step in understanding things is knowing motivation behind the theorem. Douglas and yunone have both probably explained the meaning behind those equations pretty well but take a look at this Wikipedia article for more historical context:

share|cite|improve this answer

If $\rm\:q\:$ and $\rm\:p = 4\:k+1\:$ are distinct odd primes then by the law of quadratic reciprocity we have

$\displaystyle\rm\quad\quad\quad\quad\ \ \frac{p-1}{2}\ =\ 2\:k\ \ \Rightarrow\ \ \left(\frac{q}{p}\right)\ \times\ \left(\frac{p}{q}\right)\ =\ (-1)^{\frac{p-1}{2}\ \frac{q-1}{2}}\: =\ 1$

Therefore we deduce that $\rm\displaystyle\ \ \left(\frac{q}{p}\right)\ =\ \left(\frac{p}{q}\right)$

So $\displaystyle\rm\ q=3,\ p = 2+3\:n\ \Rightarrow\ \left(\frac{3}{p}\right)\ =\ \left(\frac{2+3\:n}{3}\right)\ =\ \left(\frac{2}{3}\right)\ =\:-1\ $ since $\rm\:2\:$ is not a square $\rm\:(mod\ 3)\:.$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.